A NARRATIVE REVIEW OF ADVANCES IN PHARMACOGENETICS AND PERSONALIZED MEDICINE IN PSYCHIATRY. - Dr. Farheen fatma; Dr.Dhruv (Student's Journal of Health Research, 2023)
The variable effectiveness and side effects demonstrated in patients who receive psychotropic drugs show that there is a need for developing personalized medicines in psychiatry. Pharmacogenetics significantly impacts the pharmacokinetics and pharmacodynamics of psychotropic drugs. In the course of this review, the role of metabolism and receptor expression in the efficacy and adverse events of psychiatric drugs is discussed. Exogenous factors that affect the therapy are discussed. Further, key challenges in the application of pharmacogenomics to personalized medicine in psychiatry are discussed, along with their potential solutions. It is concluded that therapeutic drug monitoring along with pharmacogenetic testing in clinical practice can help devise personalized tailored treatment plans which can improve the mental health and quality of life of an individual and maintain a high benefit-to-risk ratio.